Analisa Alat Pengering Ikan Solar Kolektor Dengan Media Penyimpan Panas Batu Spli - Afdal Faisal; Yolli Fernanda; Arwizet K; Primawati Primawati (Jurnal Vokasi Mekanika (VoMek), 2025)
The use of solar energy as an alternative energy source has developed significantly in various applications. The fish dryer in this study utilizes solar energy, assisted by a solar collector, which uses split stones as a heat storage medium. The aim of this research is to enhance the usage of the solar collector fish dryer because it can be used when there is insufficient solar energy. The research method includes the design and creation of a dryer prototype, as well as measuring the temperature of incoming and outgoing air, including the relative humidity inside the drying chamber. The results revealed that utilizing split stones as a heat storage medium can maintain the air temperature in the drying chamber at an optimal level for a longer period, even with varying sunlight intensity. This research was conducted at the Mechanical Engineering Laboratory of Universitas Negeri Padang. The highest temperature achieved in the solar collector fish dryer with a heat storage medium in the oven or drying chamber was 40°C at 13:00 WIB, with a solar intensity of 503 W/m². The drying process of salted fish using split stones as a heat storage medium resulted in a moisture evaporation rate of 49.25% - 64.7% over 8 hours, with a drying rate of 0.068 g/m - 0.079 g/m. The collector's efficiency was 16.6% on the first day and 16.48% on the second day of testing.